Performance of dairy heifers fed high forage diets supplemented with bambermycins, lasalocid or monesin - A. Hammond; Michael V. Scheffel; Evan C. Titgemeyer; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2002)
One hundred and twenty Holstein heifers weighing approximately 450 lb at the beginning of the study were used to evaluate the impact of bambermycins (Gainpro®), monensin (Rumensin®), and lasalocid (Bovatec®) on performance when included in high forage diets fed ad libitum. Heifers were housed in 24 pens (5 hf/pen) containing a super hutch. Pens were blocked (3 pens/block) from heaviest to lightest and randomly assigned within blocks to bambermycins, lasalocid, or monensin treatment. Bambermycins, lasalocid, and monensin were mixed with fine ground corn and fed as topdressing to deliver 20.25, 150, and 150 mg/hd daily, respectively. Diets were formulated (NRC 2001) to support body weight gains of less than 2 lb/hd daily using a mix of chopped alfalfa hay and corn silage (lighter weight heifers) or chopped alfalfa hay, chopped prairie hay, and corn silage (heavier weight heifers) supplemented with a mineral/vitamin premix. All heifers were fed a common total mixed ration, differing only in topdressing. Diets were fed once daily for ad libitum intake. The study continued until the average bodyweight exceeded 800 lbs. (140 days on study) at which time they were inseminated and first service conception rate determined. Heifers fed monensin consumed less dry matter (DMI) (P<0.05) than those fed bambermycins and lasalocid during the periods d 29 to 56, 57 to 84, and 113 to 140 but DMI was similar across treatments during the 140- day study. No differences were observed for ADG over the 140-d study but heifers fed bambermycins and monensin tended (P=0.06) to gain faster during days 85 to 112 than heifers fed lasalocid. Feed efficiency (gain/feed) varied, but heifers consuming diets containing bambermycins and monensin were more efficient (P<0.05) during days 85 to 112 and tended to be more efficient (P=0.051) during the 140- day study than heifers consuming lasalocid. Bodyweight, condition score, and hip height were similarly influenced by dietary treatments. First service conception rates were 60, 47 and 55% for heifers fed bambermycins, lasalocid, and monensin, respectively.; Dairy Day, 2002, Kansas State University, Manhattan, KS, 2002;
Keywords: Dairy Day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-121-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 898; Dairy; Inophores; Growth; Heifers